Implementation of Inside, Outside and Circle (IOC) Based RPP to Increase Student Learning Motivation in Fiqh Subjects - Wahyudi, Wahyudi; M., Aliyul Wafa; Aliyuddin, Aliyuddin (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Fiqh lessons are very important lessons for students to understand. So it is appropriate for learning to receive attention in improving the quality of fiqi learning. This research aims to improve the learning process and increase student learning outcomes in fiqh subjects by implementing the inside outside circle learning plan model. This research method is classroom action research in class XI Madrasah Aliyah Darun Najah Karangploso Malang with a total of 22 students, the research consists of two cycles. The data collection technique was carried out using qualitative descriptive observation sheets, while students' learning outcomes tests were carried out through daily tests with each cycle analyzing the average score of student learning outcomes by comparing the scores before the action and after the action. The results of the research showed that there was an increase in student motivation and learning outcomes in the fiqh subject for class XI students at Madrasah Aliyah Darun Najah Karang ploso Malang. This can be seen from the average score of learning outcomes for students' fiqh lessons which has increased, namely (55.5) in the basic score, increasing to (65.8) in the first daily test then to (79.3) in the second daily test (85.4). ) . The learning process shows improvement, students are increasingly enthusiastic in participating in the learning process, but the problem that occurs is that time is often lacking in the learning process. So it can be concluded that the implementation of the inside outside circle model learning process plan can increase student motivation and learning outcomes in the Fiqh subject for class XI students at the Aliyah Darun Najah Karangploso Malang madrasah.